Asean Comprehensive Security in Managing Covid-19 Pandemic In Myanmar - Rahmadanu Pradityo (Universitas Negeri Medan, 2022)
The COVID-19 pandemic has globally affected all people’s life aspects in every country in the world, including the Southeast Asian region. Not all countries can have stable domestic capabilities and conditions to face COVID-19 as happened in Myanmar. Their domestic situation has been negatively impacted by conflicts between the community and the government. The people of Myanmar are exacerbated by the coup by the Myanmar military against the legitimate government. This has caused the political and security situation in Myanmar to become chaotic because Myanmar people who oppose the military junta stage demonstrations that triggered the military junta to be repressive by arresting the protesters including health workers, teachers, and others. This results in less optimal handling of the COVID-19 pandemic and causes the spread of COVID-19 is getting worse and out of control. Therefore, ASEAN which is a regional organization in South East Asia has decided to take strategic steps to make the spread of the virus remain under control in the region, especially Myanmar. This article describes ASEAN's approach to Myanmar in tackling COVID-19 and providing humanitarian assistance to the Myanmar people who are struggling during an unstable situation. This research uses a comprehensive security concept framework with a qualitative approach. The data are collected using literature studies consisting of books, journal articles, official ASEAN and government websites, and online news sites. The results show that ASEAN has taken an approach with its typical characteristics to cope with COVID-19 amid pressure and criticism from state and non-state actors toward Myanmar.